Care and Do Not Harm: Possible Misunderstandings With Quaternary Prevention (P4); Comment on "Quaternary Prevention, an Answer of Family Doctors to Over Medicalization" - Daniel Widmer (Kerman University of Medical Sciences, 2015)
The discussion between general practitioners (GPs) and healthcare delivery organizations necessitates a common language. The presentation of the 4 types of GP's activities, opens dialogue but can lead to possible misunderstandings between the micro- and macro-level of the healthcare system. This commentary takes 4 examples: costs reduction by P4, priority of beneficence or nonmaleficence, role of evidence-based medicine (EBM) and use of a constructivist model.